Aplikasi Penuntun Shalat Sunnah Berbasis Android - Qamaruzzaman, M. Haris (STMIK Palangkaraya, 2016)
Sunnah prayer is all done outside of prayer difardhukan. Sunnah prayers called salat or prayer nawaafli naafilah. Rasulullah SAW. always sunnah prayers both in daylight and at night. All the sunnah prayer is done it is to get closer to Allah SWT and expects additional reward more. And also to increase the devotion to Allah SWT. Various sunnah prayer also has fadhilah or benefits, both in matters of the world and the hereafter. One fadhilahnya is closer to Allah SWT and encourage a loved Allah SWT. It required an application as a medium in order to provide more complete information to the public about the sunnah prayers. In this study successfully implemented an Application-Based Guidance Sunnah Android Salah and has been tested against the results of the implementation. With this application, people can be facilitated in finding information about the sunnah prayers and may provide users of this application on the comprehension and understanding of the sunnah prayers. Based on the results of the respondents to produce a percentage of 86%, which means more than good. Thus this application can send information about the sunnah prayers to the wider community.